In Vivo Study of the Antibacterial Chitosan/Polyvinyl Alcohol Loaded with Silver Nanoparticle Hydrogel for Wound Healing Applications - Tan Dat Nguyen; Thanh Truc Nguyen; Khanh Loan Ly; Anh Hien Tran; Thi Thanh Ngoc Nguyen; Minh Thuy Vo; Hieu Minh Ho; Ngoc Thao Nhi Dang; Van Toi Vo; Dai Hai Nguyen; Thi Thu Hoai Nguyen; Thi Hiep Nguyen (International Journal of Polymer Science)
Silver nanoparticles have attracted great interests widely in medicine due to its great characteristics of antibacterial activity. In this research, the antibacterial activity and biocompatibility of a topical gel synthesized from polyvinyl alcohol, chitosan, and silver nanoparticles were studied. Hydrogels with different concentrations of silver nanoparticles (15 ppm, 30 ppm, and 60 ppm) were evaluated to compare their antibacterial activity, nanoparticles’ sizes, and in vivo behaviors. The resulted silver nanoparticles in the hydrogel were characterized by TEM showing the nanoparticles’ sizes less than 22 nm. The in vitro results prove that the antibacterial effects of all of the samples are satisfied. However, the in vivo results demonstrate the significant difference among different hydrogels in wound healing, where hydrogel with 30 ppm shows the best healing rate.